Simplified input-output inversion control of a double pendulum overhead crane for residual oscillations reduction - Giacomelli, M.; Padula, Fabrizio; Simoni, L.; Visioli, A. (Permagon, 2018)
© 2018 Elsevier Ltd In this paper we present the application of an input-output inversion technique for the open-loop control of an overhead crane modelled as a double pendulum. The method is mathematically derived, obtaining a parametric trajectory that ensures reduced residual oscillations. Then, it is shown that the postactuation can be neglected so that the method can be implemented with standard industrial drives. The robustness of the method is evaluated by means of simulations, and the performance of the method is experimentally compared with the well-known input shaping technique. The advantages of using a double pendulum model instead of a simple pendulum one are also shown.